Effect Of Intracameral Phenylephrine And Ketorolac 1.0%/0.3% On Intraoperative Pain And Opioid Use During Cataract Surgery - Donnenfeld ED (Dove Medical Press, 2019)
Eric D Donnenfeld,1 Ryan D Shojaei2 1Department of Ophthalmology, New York University, New York, NY, USA; 2Ophthalmic Consultants of Long Island, Westbury, NY, USACorrespondence: Eric D DonnenfeldOCLI, 711 Stewart Avenue, Suite 160, Garden City, NY 11530, USATel +1 516 500 4200Fax +1 516 742 0017Email ericdonnenfeld@gmail.comPurpose: To compare the effect of Omidria (phenylephrine and ketorolac 1.0%/0.3%) vs epinephrine on pain reduction and opioid usage during cataract surgery.Patients and methods: Sixty patients at a single center underwent femtosecond laser (FLACS) or conventional phacoemulsification under topical lidocaine gel anesthesia and intracameral preservative-free lidocaine 1%. Eligible participants were prospectively assigned to receive either intracameral phenylephrine and ketorolac 1.0%/0.3% or intracameral epinephrine. All patients received standardized pre- and post-operative topical therapy. Intravenous (IV) fentanyl was administered for ocular discomfort in patients who complained of intraoperative pain. Outcome measures included both pain (measured by mean visual analog scale (VAS) pain scores from 0 (no pain) to 10 (extreme pain)) and the use of IV fentanyl during surgery. A composite endpoint identified “responders” as being patients who: (1) did not require fentanyl and (2) experienced no to minimal pain (VAS score ≤ 3).Results: Forty-one patients were in the phenylephrine and ketorolac 1.0%/0.3% (study) group and 19 were in the epinephrine (control) group. Mean VAS pain scores were significantly (48.9%) lower in the study group than the control group (2.3 vs 4.5; P < 0.0001). The proportion of patients with VAS scores ≤ 3 was significantly greater in the study group (85.0%) than the control group (31.6%) (P < 0.0001). A smaller proportion of patients required intraoperative fentanyl in the study group compared to the control group (9.8% vs 42.1%; P = 0.006). For the composite endpoint, patients receiving phenylephrine and ketorolac 1.0%/0.3% were 94% less likely to require fentanyl or to have moderate-to-severe pain (pain VAS ≥ 4; OR, 0.06; 95% CI 0.02–0.24) than patients receiving epinephrine.Conclusion: Our results suggest that the routine use of intracameral phenylephrine and ketorolac 1.0%/0.3% during cataract surgery can significantly reduce patient pain as well as the need for opioids.Keywords: epinephrine, Omidria, ketorolac, phacoemulsification, FLACS